Leaching efficiency and kinetics of the recovery of palladium and rhodium from a spent auto-catalyst in HCl/CuCl2 media - Nogueira, Carlos A. (2020)
The recycling of scarce elements such as platinum-group metals is becoming crucial due to their growing importance in current and emerging applications. In this sense, the recovery of palladium and rhodium from a spent auto-catalyst by leaching in HCl/CuCl2 media was studied, aiming at assessing the kinetic performance as well as the influence of some processing factors, and the behaviour of contaminant metals. Based on a kinetic model developed for the present case, the influence of temperature was evaluated and the corresponding values of activation energy were estimated as 60.1 ± 4.1 kJ mol-1 for Pd and 44.3 ± 7.3 kJ mol-1 for Rh, indicating the relevance of the chemical step rather than diffusion. This finding was corroborated by the non-significant influence of the stirring velocity. The reaction orders were estimated for each leaching reagent: for HCl, values of 2.1 ± 0.1 for Pd and 1.0 ± 0.3 for Rh were obtained; for Cu2+, the obtained values were 0.42 ± 0.04 for Pd and 0.36 ± 0.06 for Rh. Without any significant loss of efficiency, solutions with higher metal concentrations were obtained using lower liquid/solid ratios, such as 5 L/kg. The main contaminant in solution was aluminum, and its leaching was found to be very dependent on the temperature and acid concentration.